Class Management in Islamic Religious Education Subjects at Islamic Middle School Karawang - Desti Rafitri; Sutarjo Sutarjo; Lilis Karyawati (Edumaspul: Jurnal Pendidikan, 2022)
Education is very important in building the nation's generation by creating advanced human resources. With this progress, there is a teacher who has a very important role in providing teaching and strategic classroom management. This study aims to describe classroom management in Islamic religious education subjects and overcome classroom management problems in SMP Islamic Karawang. The study used a descriptive qualitative approach, the subject of the study was aimed at Islamic religious education teachers and students. The data collection technique in this writing uses interview, observation, and documentation techniques. The results of this study indicate that there are several classroom management, namely, preparing rules in the classroom, making procedures for items in the classroom, and preparing learning activities by preparing absenteeism and student assessment books. While the way to overcome classroom management problems is to show a responsive attitude, pay attention to all students, and reprimand if there are violations.